Prevalence and predictors of latent tuberculosis infection among Italian State Policemen engaged in assistance to migrants: a national cross-sectional study. Issue 10 (3rd October 2016) - Durando, Paolo; Garbarino, Sergio; Orsi, Andrea; Alicino, Cristiano; Dini, Guglielmo; Toletone, Alessandra; Ciprani, Fabrizio; Conte, Giuseppe; Santorsa, Roberto; Icardi, Giancarlo
Abstract : Objectives: Better knowledge about tuberculosis (TB) and latent TB infection (LTBI) epidemiology is a crucial step for the development of effective strategies towards the control and elimination of this deadliest and persistent health threat. No study has investigated LTBI epidemiology in policemen who act as an interface with cross-border migrants. Methods: A survey to measure the LTBI prevalence and assess the demographic, professional and clinical features potentially associated with tuberculin skin test (TST) positivity was performed in Italian State Police (ISP) employees engaged, even occasionally, in relief activities, hospitality, photographical identification, escorting and accompanying of migrants, regardless of contact with active TB cases. Variables potentially associated with TST positivity were evaluated with univariate and multivariate analysis. Results: From September to December 2014, 4225 ISP workers underwent TST screening and completed the questionnaire for data collection, according to study procedures. The TST was positive in 9.9% of individuals: no active TB cases were registered among the entire study population. Age, previous BCG vaccination and work category resulted independently associated with TST positivity. Conclusions: This is the first study providing updated data about LTBI epidemiology among ISP employees engaged in assistance to migrants and furnish preliminary evidence of possible associations between TST positivity and different conditions that need to be deeply investigated with prospective studies.